EVALUATION OF QUALITY ATTRIBUTES OF PROPRANOLOL SPLIT TABLETS: FOCUS ON DOSE VARIABILITY - Eserian, Jaqueline Kalleian; Lombardo, Márcia (Infarma - Ciências Farmacêuticas, 2017)
Tablet splitting is a widespread practice among patients and health professionals aiming the administration of lower doses and the reduction of the cost of prescriptions. Nevertheless, potential concerns such as weight variation, stability and uneven drug content of the halves are related to this practice. The objective of this study was to evaluate the uniformity of half-tablets regarding weight and drug content in three different commercial products containing propranolol. Also, it was assessed drug content for whole tablets. Weight variation and drug content uniformity tests were evaluated for whole and split tablets, as well as the weight loss due to the splitting process. Drug content evaluation for whole tablets showed that all products were satisfactory. All the products were approved in the weight variation and drug content uniformity tests before splitting, with results close to 100%, but the halves of all products failed the tests, presenting a high variability between the portions. In one of the products, halves ranged from 75.5 to 120.4% of the target drug content, indicating that when administered to patients, daily doses may vary around 45%. Splitting propranolol tablets might compromise clinical treatment, affecting blood pressure and consequently producing side effects. Clinical implications due to tablet splitting might not be critical in some cases. Nevertheless, the high variability between doses should be considered by healthcare professionals when prescribing a therapy involving this practice.